A Place-Based Approach in EU Regional Development and Its Application in Latvia - Baltiņa Līga (Baltic Journal of European studies, 2014)
The EU’s regional development policy is gradually moving from the redaction of regional disparities towards regional development growth. The role and involvement of regional and local authorities in regional development policy is increasing. Global changes and challenges call for a growing need to develop more efficient regional development policy instruments that would result in growth and increased quality> of life. Place-based approach is a strategic approach aimed at the development of territorial resources. The aim of this research is to evaluate the role of place-based approach in regional development, to identify and assess the main elements and opportunities brought by the implementation of such an approach.